2020
DOI: 10.1159/000506159
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Intraluminal Thrombus Makes Saccular Aneurysm More Biologically Active than Fusiform in an Experimental Rat Model

Abstract: Introduction: Saccular aneurysms are thought to have a worse prognosis than fusiform aneurysms in humans, due to hemodynamic reasons. However, data comparing hemodynamic and biology in saccular and fusiform aneurysms are lacking. The main objective was to evaluate the impact of aneurysm morphology on intra-luminal thrombus (ILT) formation and activity. Methods: Forty Lewis rats were randomly divided into 2 groups of 20: "saccular" (Group A) and "fusiform" (Group B) aneurysms. Decellularized thoracic aortas fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…Myeloperoxidase, which is partially released by activated platelets, was localized both on the surface of and inside platelets. Etienne et al found that myeloperoxidase was significantly elevated in experimental saccular aneurysms compared with fusiform aneurysms in a decellularized xenograft model in rats [ 70 ], and it caused oxidative damage by producing superoxide in a chronic remodel of AAA [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Myeloperoxidase, which is partially released by activated platelets, was localized both on the surface of and inside platelets. Etienne et al found that myeloperoxidase was significantly elevated in experimental saccular aneurysms compared with fusiform aneurysms in a decellularized xenograft model in rats [ 70 ], and it caused oxidative damage by producing superoxide in a chronic remodel of AAA [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a rat xenograft model, Etienne et al 50 created saccular or fusiform aneurysms. They showed that saccular aneurysms had lower inflow velocities, greater vortex flow, and thicker ILT, when assessed by magnetic resonance imaging, compared with fusiform aneurysms.…”
Section: Mechanical Properties and Hemodynamics Of Iltmentioning
confidence: 99%
“…This is the case for contractions following ineffective extrasystoles, 7 or exercise, which causes an increase in catecholamine levels. Aneurysms (eg, intracranial saccular aneurysms) are characterized by bidirectional intrasaccular blood flow and shear force 18 that induce endothelial dysfunction, and thrombus formation within the lumen, but also enhanced retention of gadolinium within the saccular wall, reflecting a significant increase in permeability. 19 The luminal surface of the endothelium is coated in a jelly-like protective layer or filter-the glycocalyx-composed of proteoglycans that are particularly rich in glycosaminoglycans.…”
Section: Adjustable Barrier Function Of the Arterial Endotheliummentioning
confidence: 99%